The Effectiveness of Using a Laboratory on Understanding Physics Concepts From Urban And Rural Schools (Pengaruh Keefektifan Penggunaan Laboratorium Terhadap Pemahaman Konsep Fisika Ditinjau Dari Sekolah Perkotaan Dan Pedesaan) - Zainuddin Zainuddin; Halmuniati Halmuniati; La Ode Asmin; La Isa (Shautut Tarbiyah, 2022)
This research aims to know (1) differences in comprehension of students ' physics concepts are reviewed from urban schools taught using real labs with Virtual laboratories (2) Differences in understanding student physics concepts from rural schools Taught using a real laboratory with a virtual laboratory at MA students in South Konawe district.This research is a quantitative study using experimental methods with a treatment by level 2 x 2 design.The subject of this study is MA students in South Konawe district consist of 4 schools determined with purposive random sampling technique.The instrument used is a deed test and a test understanding of physics concept.Data analysis techniques used using T-Test tests are of 5% significance. The results of this study were obtained (1) There are differences in understanding concepts Student physics taught using a real laboratory with a virtual lab reviewed from urban schools in the MA district of South Konawe, and (2) There are no differences in understanding the physics concept of students being taught using a real laboratory with Virtual Laboratory of the school in the countryside at MA in South Konawe district.Keywords: real labs, virtual labs, understanding the physics concept